Mechanical behaviour of wood T-joints. Experimental and numerical investigation (Fracture and Structural Integrity, 2014)
Results of a double-shear single-dowel wood connection tested under monotonic quasi-static compression loading are presented and discussed in this paper. The wood used in this study was a pine wood, namely the Pinus pinaster species, which is one of the most important Portuguese species. Each connection (specimen) consists of three wood members: a centre member, loaded in compression along the parallel-tograin direction and two simply supported side members, loaded along the perpendicular-to-grain direction (Tconnection). The load transfer between wood members was assured by means of a steel dowel, which is representative of the most common joining technique applied for structural details in wooden structures. The complete load-slip behaviour of the joint is obtained until failure. In particular, the values of the stiffness, the ultimate loads and the ductility were evaluated. Additionally, this investigation proposed non-linear 3D finite element models to simulate the T-joint behaviour. The interaction between the dowel and the wood members was simulated using contact finite elements. A plasticity model, based on Hill’s criterion, was used to simulate the joint ductility and cohesive damage modelling was applied to simulate the brittle failure modes (splitting) observed in the side members of the joint. The simulation procedure allowed a satisfactory description of the non-linear behaviour of the T-joint including the collapse prediction.
Keywords: Maritime pine wood